The neoinstitutional perspective approach for developing countries’ companies’ internationalization processes - Silva, Luciano Messina Pereira da; Lopes, Fernando Dias (Revista de Administração da UFSM, 2018)
This theoretical essay seeks to associate the current knowledge of internationalization processes that considers economic aspects as motivators and cultural aspects as barriers, with aspects related to the Institutional Theory. Institutional theory concepts aren’t considered thoroughly when dealing with country level variables regarding to internationalization processes, and these authors barely study institutions’ influence in the internationalization process of a given company. A review of literature regarding internationalization processes and institutional theory was performed, and it was complemented by an approach that assumes an institution-based view complementing the industry-based view and resource-based view for internationalization strategy, forming the strategy tripod. The literature review also considers the influence of the institutional environment when a multinational company chooses the entry mode in a new country. It concludes that the presence of institutional aspects is at least implied when dealing with cultural issues in internationalization processes and cannot be disregarded.